Using the Go-Lab Platform as a Media in Science Learning - Fuad Tamami; Rahmatullah Rahmatullah (Indonesian, 2021)
Learning science has observations to make. This can be done using the help of technology, one of which is Go-Lab. The use of this technology in addition to helping educators to convey the material to be conveyed, technology can also be used for everything that is separated by distance. This article aims to provide information about using the Go-Lab platform for online science learning. The study conducted is a literature study of several articles related to the use of Go-Lab. Go-Lab is a platform that contains applications, virtual laboratories, and Inquiry Learning Spaces (ILS) that can be developed and used freely by teachers. Science learning using Go-Lab is provided through ILS which is designed to combine materials, applications, and virtual laboratories to support inquiry learning. The use of Go-Lab in science learning is said to be effective because of the facilities for inquiry activities, especially during the distance learning period. Further research on the use of the Go-Lab platform in science learning needs to be carried out considering the role of information technology for teaching and learning activities is a challenge during the current COVID-19 pandemic.